2020
DOI: 10.1111/clr.13619
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge preservation and early implant placement at maxillary central incisor sites: A prospective case series study

Abstract: Purpose To assess whether alveolar ridge preservation (ARP) with 90% deproteinized bovine bone mineral in a 10% collagen matrix (DBBMC) and resorbable type I/III porcine collagen matrix (CM) maintains sufficient bone volume for early implant placement 8–10 weeks after extraction of maxillary central incisors. Materials and Methods In this case series study of 10 consecutively enrolled patients, sockets of maxillary single central incisors requiring extraction and early implant placement were grafted with DBBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…scores. In contrast, a recent case series applying early implant placement in 10 patients after ARP revealed a median PES score of 10 at one-year follow-up (Chen & Darby, 2020). Moreover, outcomes from a prospective study also revealed higher PES scores (Arora & Ivanovski, 2018).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…scores. In contrast, a recent case series applying early implant placement in 10 patients after ARP revealed a median PES score of 10 at one-year follow-up (Chen & Darby, 2020). Moreover, outcomes from a prospective study also revealed higher PES scores (Arora & Ivanovski, 2018).…”
Section: Discussionmentioning
confidence: 83%
“…Those lower PES scores compared with the present findings are most likely explained by the lack of papillary tissues observed in that study resulting in decreased PES scores. In contrast, a recent case series applying early implant placement in 10 patients after ARP revealed a median PES score of 10 at one‐year follow‐up (Chen & Darby, 2020 ). Moreover, outcomes from a prospective study also revealed higher PES scores (Arora & Ivanovski, 2018 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Alveolar fissure bone grafting can fill and repair the gap of alveolar fissures, with the purpose being to rebuild the defect of the alveolar fissure so as to facilitate the emergence of cusp teeth ( 11 ). According to the time of bone grafting, alveolar ridge bone grafting can be divided into early stage (before 2 years old), early stage (2–5 years old), second stage (6–15 years old), and late stage (after 16 years old) ( 12 ). In this study, 8 patients were late stage II, and the remaining 12 patients were stage II, including 15 patients with tooth malformation extraction and loss of development in the bone graft area.…”
Section: Discussionmentioning
confidence: 99%